A CRITICAL DISCOURSE ANALYSIS OF PARTS OF SPEECH FROM TED-TALK VIDEO: HOW LANGUAGE SHAPES THE WAY WE THINK - Rizkia Ulfah; Didin Nuruddin Hidayat (Journal of Language, Literature and Teaching, 2020)
The aim of the study is to identify the use of parts of speech in speaking. In this study, the descriptive qualitative method was used to find and analyze types of parts of speech from the speaker’s talk. This study is based on Critical Discourse Analysis which was developed from the Systematic Functional Grammar (Halliday, 1971). In the current study, within a descriptive qualitative, critical discourse analysis approach was used. The data were taken from the TED-Talk video. The findings show that the speaker employs various types of parts of speech. Also, it can be identified that the use of modal verbs helps the speaker to be close to the audience while communicating the point of view relating to the topic. Moreover, personal pronouns may shorten the distance between the speaker and listeners on the event. Furthermore, using personal pronouns can help the speaker focus on the topic and associate the words into the real context.